Does the Quality of Electricity Matter? Evidence from Rural India - Ujjayant Chakravorty; Martino Pelli; Beyza Ural Marchand (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper estimates the returns to household income due to improved access to electricity in rural India. We examine the effect of connecting a household to the grid and the quality of electricity, defined as hours of daily supply. The analysis is based on two rounds of a representative panel of more than 10,000 households. We use the district-level density of transmission cables as instrument for the electrification status of the household. We find that a grid connection increases non-agricultural incomes of rural households by about 9 percent during the study period (1994-2005). However, a grid connection and a higher quality of electricity (in terms of fewer outages and more hours per day) increases non-agricultural incomes by about 28.6 percent in the same period.
Keywords: O12; O18; Q48; 330; electricity supply; quality; India; energy and development; infrastructure